Genuine motorische Phänomene bei schizophrenen Psychosen: Neuronale Korrelate und Pathomechanismen = Genuine motor phenomena in schizophrenia : neuronal correlates and pathomechanisms - Hirjak, Dusan; Thomann, Philipp; Kubera, Katharina Maria; Wolf, Robert Christian (Der Nervenarzt, 2018)
Despite a growing body of evidence on motor dysfunction in schizophrenia spectrum disorders, the neuronal correlates of genuine motor abnormalities (GMA) are not fully elucidated at present. Moreover, the clinical relevance of a potential “motor intermediate phenotype” remains controversial. This systematic review aims at characterizing a “motor intermediate phenotype” in schizophrenia spectrum disorders. The second goal of this systematic review is to discuss GMA-associated brain alterations as potential biomarkers of psychosis risk syndrome and manifest motor symptoms against the background of current neuroimaging evidence. The detailed clinical assessment of GMA in the context of multimodal imaging could, in the future promote the early recognition of psychotic disorders and the initiation of disorder-oriented and individualized treatment. Taken as a whole the data provide initial evidence that motor dysfunction in schizophrenic spectrum disorders must be considered dimensionally. The predictive value of neurobiological results with respect to the transition to a life-threatening catatonia or the development of chronic dyskinesia, cannot currently be conclusively assessed.
Gesehen am 04.09.2019
Online publiziert:13. November 2017